From Amine , Synthesis and Characterization of New Some Transition and Non-Transition Elemnts Metal Dinuclear Complexes Derived Schiff Base ligand 1- Chloro – 2- ( 2- chroroethoxy) Ethan - Mahammed, Modhir Y.; Jabbar, Salwa A.; Shanak, Kader A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This research of the thesis includes the preparation and identification of two new tetra dentate Schiff’s base ligand . (H4L1 ) and then binuclear complexes with a group of transition metal ions in addition to cadmium with the general formula. [M2(L1)Cl2(H2O)2] M+2=[Mn,Co,Ni,Cu and Cd] The prepared complexes and ligands were identified by in pared(FT-IR) spectroscopy ,Ultra violet-visible(UV-visible) spectroscopy and H-NMR spectroscopy of the prepared ligand, also microanalysis (C.H.N) of some of the prepared compounds has been carried out and the melting points, the molar conductivity and magnetic susceptibility